Profile of Women Incarcerated For Murder in Oklahoma - Fletcher, Beverly (1994)
The present study addresses the need to increase our understanding of women incarcerated for violent crimes, especially murder, by developing a profile of women incarcerated for murder in Oklahoma. Compared to the United States as a whole, Oklahoma has one of the highest per capita rates of female incarceration. While women represent only five percent of the total prison population in the United States, they comprise twelve percent of Oklahoma's prison population (Oklahoma Department of Corrections, 1989). Survey data of female inmates in Oklahoma are utilized to study the demographic 45 - characteristics as well as the current and past personal and family background factors of women incarcerated for murder. In addition, recommendations are offered to address the specific needs of women incarcerated for Murder